Safety of full bowel preparation and colonoscopy in elderly patients with ulcerative colitis: A real‐world multicenter retrospective cohort study - Yu Hashimoto; Shiko Kuribayashi; Yuki Itoi; Keigo Satou; Kou Nakata; Kengo Kasuga; Hirohito Tanaka; Hiroko Hosaka; Takashige Masuo; Kyoko Maruhashi; Kensuke Furuya; Tomoyuki Masuda; et al. (DEN Open)
Abstract Background The number of elderly patients with ulcerative colitis (UC) has been increasing worldwide. Complications are common in elderly patients who undergo colonoscopy, raising doubts about whether colonoscopy should be performed in the same way in this age group as in younger patients. The aim of this study was to determine the safety of full bowel preparation and colonoscopy in elderly patients with UC. Methods We retrospectively reviewed a cohort of patients with UC who had visited any of the 12 hospitals and were registered in our inflammatory bowel disease database. We compared complications associated with colonoscopy and bowel preparation and relapse of UC after colonoscopy in 133 patients aged ≥65 years with UC (the elderly group) and 116 randomly selected patients aged <65 years with UC (the non‐elderly group). Results Nine elderly patients were not referred for colonoscopy by their physicians because of poor performance status or advanced age. There was no significant between‐group difference in the complication rate (p = 0.57) or frequency of relapse of UC after colonoscopy (p = 0.67). Conclusions The findings of this study indicate that colonoscopy can be performed as safely in elderly patients with UC as in their younger counterparts. However, our results also indicate that colonoscopy is often avoided in elderly patients, possibly because of concerns about safety.